Legal mobilization - Druliolle, Vincent (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The article analyzes the phenomenon of legal mobilization, or the use of litigation by social movements and, above all, the extent to which their discourse draws on the law. After a brief introduction of the evolution of the study of legal mobilization and its main concepts, the third section focuses on the analysis of legal framing, a key aspect of legal mobilization. The following section illustrates how this theoretical framework can help us explain the evolution of the struggle of the movement for the recovery of historical memory in Spain. Finally, the conclusion outlines a few reflections about legal mobilization and its study.